KEBERFUNGSIAN SOSIAL PENERIMA MANFAAT GRADUASI MANDIRI PROGRAM KELUARGA HARAPAN (PKH) DI KOTA LUBUKLINGGAU - Setiawati, Ida Agus; Yunilisiah, Yunilisiah; Adhrianti, Lisa (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
The Family Hope Program (PKH) is one of the conditional social assistance programs aimed at improving the living standards of poor families. In its implementation, there are a number of beneficiaries who have graduated independently, meaning they have stopped receiving assistance on their own initiative and ability. This study aims to analyse the social functioning of PKH beneficiaries who have graduated independently. The study focuses on economic, social, and psychological aspects of their lives post-graduation. The research method used is descriptive qualitative with a case study approach. The results of the study indicate that the majority of individuals who have graduated independently demonstrate positive social functioning, including increased economic independence, involvement in social activities, as well as increased self-confidence and motivation for self-reliance.